2019
DOI: 10.4103/ija.ija_745_18
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wound infiltration of bupivacaine at two different anatomical planes for caesarean analgesia – A randomised clinical trial

Abstract: Background and Aims: Continuous wound infiltration of local anaesthetics provide postoperative analgesia by peripheral nociceptors blockade.The placement of wound infiltration catheter in the optimal anatomical plane of surgical wound may play a significant role in reducing postoperative pain depends on the surgical procedure. We hypothesised that preperitoneal infusion of local anaesthetics will reduce the postoperative opioid consumption as compared to subcutaneous infusion following cesarean se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Our results displayed that group B had significantly longer hospital stay duration compared to group A (P<0.001). The average duration of hospital stay was 5.52 ± 0.87 days in the subcutaneous group and 5.32 ± 0.69 days in the preperitoneal group, (P = 0.37) (24) . Regarding incidence of PONV, comparable to our findings, a study concluded that the overall incidence of nausea was greater in controls (1 1 of 35) than for those given bupivacaine (3 of 35) (p=O.O46).…”
Section: Discussionmentioning
confidence: 93%
“…Our results displayed that group B had significantly longer hospital stay duration compared to group A (P<0.001). The average duration of hospital stay was 5.52 ± 0.87 days in the subcutaneous group and 5.32 ± 0.69 days in the preperitoneal group, (P = 0.37) (24) . Regarding incidence of PONV, comparable to our findings, a study concluded that the overall incidence of nausea was greater in controls (1 1 of 35) than for those given bupivacaine (3 of 35) (p=O.O46).…”
Section: Discussionmentioning
confidence: 93%
“…Some investigators have also used continuous infusion techniques by putting catheters. 12 Nanze YU et al conducted a meta-analysis including 4 RCTs where they compared analgesic effect of TAP block with WSI in lower abdominal surgeries including caesarean section. They concluded that both have short term (up to 24 hours) analgesic effect but TAP block provide better analgesia by having lower pain scores, lesser need of rescue analgesics and opioid consumptions compared WSI which were consistent with our study results.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of information on the bioavailability of local anesthetics, especially bupivacaine, administered preperitoneally and the risks associated with their systemic resorption, it seems important to have serum dosages during prolonged continuous infusions. Despite various articles reviewing the efects of wound infltration technique on pain control and outcomes, only a few report complications and limitations [10][11][12][13]; systemic toxic efects and plasma concentrations of local anesthetics have not been studied in most cases.…”
Section: Introductionmentioning
confidence: 99%